Specific cleavage of human type III and IV collagens by Pseudomonas aeruginosa elastase. - Heck, L W (1986)
Purified Pseudomonas aeruginosa elastase cleaved human type III and IV collagens with the formation of specific cleavage products. Furthermore, type I collagen appeared to be slowly cleaved by both P. aeruginosa elastase and alkaline protease. These cleavage fragments from type III and IV collagens were separated from the intact collagen chains by SDS polyacrylamide gradient gel electrophoresis run under reducing conditions, and they were detected by their characteristic Coomassie blue staining pattern. The results of these studies suggest that the pathogenesis of tissue invasion and hemorrhagic tissue necrosis observed in P. aeruginosa infections may be related to the degradation of these collagen types by bacterial extracellular proteases.